Battery Technologies: Micro‐Patterned Lithium Metal Anodes with Suppressed Dendrite Formation for Post Lithium‐Ion Batteries (Adv. Mater. Interfaces 11/2016). Issue 11 (7th June 2016) - Park, Joonam; Jeong, Jiseon; Lee, Yunju; Oh, Min; Ryou, Myung‐Hyun; Lee, Yong Min
Abstract : In article 1600140, Myung‐Hyun Ryou and Yong Min Lee suggest that the well‐designed surface‐patterns on Li metal may resolve the chronic Li dendrite formation problem of Li metal electrodes, which restricted the implementation of Li metal in a practical secondary battery system over five decades.